School learning of students with intellectual disabilities in Youth and Adult Education (EJA): discussions and implications (Práxis Educativa, 2023)
This article aims to discuss the school learning of students with intellectual disabilities, in the final grades of Elementary School and Education for Young and Adults in High School (known in Brazil by the acronym EJA). The study is based on Lev Semionovitch Vygotsky (1997, 2007, 2011, 2021), Leite (2020), Nascimento (2017) and Trentin (2018). The research, of qualitative approach, was developed through a case study, with the participation of three students with intellectual disabilities and ten teachers from a State Center of Basic Education for Young and Adults, in the State of Paraná. The data obtained through semi-structured interviews (students) and an open questionnaire (teachers) were analyzed using the Content Analysis. The following results are highlighted: a) the search for school learning in EJA is motivated by work and social participation; b) for students and teachers, mediation by the other and the Specialized Educational Service (SES) contribute to school learning; c) SES and teacher training for EJA need to be rethought.Keywords: Youth and Adult Education. Intellectual disability. Inclusive education.